Peat Stabilization by Using Ordinary Portland Cement (OPC) Mixed with Rice Husk Ash (RHA) - Abu Talib, Mohd Khaidir; Arifin, Siti Nor Hidayah; Zainorabidin, Adnan; Md Yusof, Zeety; Mohammad Noh, Noorasyikin; Basri, Kasbi (International Journal of Integrated Engineering, 2024)
The condition of peat soil that has a high organic and water content causes the strength of peat soil to be at a very weak to bear any load. The use of binders such as cement in peat soil stabilization methods can increase the strength of the soil, but the use of cement in large quantities will result in environmental pollution. This study was conducted to obtain the optimal percentage of Rice Husk Ash (RHA) as a replacement material of cement. Test of the basic characteristics of peat soil is carried out in order to identify the nature of peat soil. The strength of treated and untreated peat soil was determined through an unconfined compression test (UCS). replacement at 15% The result of the study shows the RHA of Ordinary Portland Cement (OPC) gave the highest strength with the value of 531 kN/m² and 580 kN/m² for 7 and 28 curing days respectively. The microstructure image shows the difference in total porosity between the untreated and treated samples through Scanning Electron Microscopy (SEM) test. A chemical test via Energy Dispersive X-Ray (EDX) shows that the strength of samples increases when the amount of carbon decreases and calcium content increases. The results of the study show that the use of discarded agricultural waste can be used as an additive in reducing the use of cement to increase the strength of peat soil based on soil stabilization methods.